A revision of the spider genus Raveniola (Araneae, Nemesiidae). II. Species from Central Asia - Zonstein, Sergei L. (European Journal of Taxonomy, 2024)
The Central Asian representatives of the spider genus Raveniola Zonstein, 1987 (Araneae, Nemesiidae) are revised. The genus is found to encompass 29 regional species: ♀ Raveniola afghana sp. nov. (Afghanistan), ♂♀ R. alajensis sp. nov. (Kyrgyzstan, Tajikistan), ♂ R. caudata Zonstein, 2009 (Tajikistan), ♂♀ R. concolor Zonstein, 2000 (India), ♂♀ R. cucullata sp. nov. (Tajikistan), ♂♀ R. diluta sp. nov. (Tajikistan), ♂♀ R. dolosa sp. nov. (Tajikistan), ♂♀ R. fedotovi (Charitonov, 1946) (Uzbekistan), ♂♀ R. ferghanensis (Zonstein, 1984) (Kazakhstan, Kyrgyzstan, Tajikistan, Uzbekistan), ♂♀ R. hirta sp. nov. (Tajikistan), ♂♀ R. ignobilis sp. nov. (Tajikistan), ♂ R. inopinata sp. nov. (Tajikistan), ♂ R. insolita sp. nov. (Tajikistan), ♀ R. karategensis sp. nov. (Tajikistan), ♂♀ R. kirgizica sp. nov. (Kyrgyzstan), ♂ R. kopetdaghensis (Fet, 1984) (Turkmenistan), ♂♀ R. mikhailovi Zonstein, 2021 (Kyrgyzstan, Uzbekistan), ♂♀ R. nenilini sp. nov. (Uzbekistan), ♂♀ R. ornata sp. nov. (Tajikistan, Uzbekistan), ♂♀ R. ornatula sp. nov. (Tajikistan), ♂ R. ovchinnikovi sp. nov. (Kazakhstan, Kyrgyzstan), ♂♀ R. pallens sp. nov. (Uzbekistan), ♂♀ R. pamira sp. nov. (Tajikistan), ♂♀ R. redikorzevi (Spassky, 1937) (Turkmenistan), ♀ R. sororcula sp. nov. (Tajikistan), ♀ R. tarabaevi sp. nov. (Kazakhstan), ♂♀ R. virgata (Simon, 1891), the type species of the genus (Kyrgyzstan), ♂♀ R. vulpina sp. nov. (Kyrgyzstan) and ♂♀ R. zyuzini sp. nov. (Uzbekistan). Redescriptions of eight previously described species are given, the descriptions of 21 above-listed new species are provided, and the female of R. redikorzevi is described for the first time. All mentioned species are assigned herein to four species groups (including two of them previously separated and another two newly established ones), which are confined exclusively to the region. Keys to the species groups and included species, as well as data on their variation, distribution and habitats, are provided.